2006
DOI: 10.1302/0301-620x.88b5.17184
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of reproducibility and accuracy in templating hybrid total hip arthroplasty using digital radiographs

Abstract: In 20 patients undergoing hybrid total hip arthroplasty, the reproducibility and accuracy of templating using digital radiographs were assessed. Digital images were manipulated using either a ten-pence coin as a marker to scale for magnification, or two digital-line methods using computer software. On-screen images were templated with standard acetate templates and compared with templating performed on hard-copy digital prints. The digital-line methods were the least reliable and accuracy of sizing compared wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 11 publications
5
33
0
Order By: Relevance
“…Intraobserver ICC values showed almost perfect agreement (ICC [ 0.8) for both acetabular and femoral components when using both templating methods, suggesting both methods are highly reproducible. Our ICC values correspond well to previous studies, which found ICC values ranging from 0.7 to 0.97 [6,10,15,21]. Our study showed that experience level did not have an effect on accuracy nor intraobserver variability.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Intraobserver ICC values showed almost perfect agreement (ICC [ 0.8) for both acetabular and femoral components when using both templating methods, suggesting both methods are highly reproducible. Our ICC values correspond well to previous studies, which found ICC values ranging from 0.7 to 0.97 [6,10,15,21]. Our study showed that experience level did not have an effect on accuracy nor intraobserver variability.…”
Section: Discussionsupporting
confidence: 92%
“…However, values were lower than that quoted by Gamble et al [10], which found ICC values ranging from 0.8 to 0.94. We found moderate interobserver ICC value agreement for the acetate templating for the acetabular component, similar to the findings of Oddy et al (ICC, 0.43-0.47) [21]. Intraobserver ICC values showed almost perfect agreement (ICC [ 0.8) for both acetabular and femoral components when using both templating methods, suggesting both methods are highly reproducible.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Different methods of scaling digital radiographs have been described and investigated to improve planning accuracy [17][18][19][20][21]. Accurate positioning of the reference ball at the level of the joint is crucial to achieving the greatest possible referencing reliability [17,22,23].…”
Section: Introductionmentioning
confidence: 99%